PENGEMBANGAN MEDIA INTERAKTIF BERBASIS KOMPUTER PADA PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR - Siti Namiroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2019)
Abstract The purpose of this study is to produce multimedia product that is useful for use in the learning process and can improve student learning outcomes. This study uses the Dick and Carey research and development methodology. The research instruments used in this study were interviews, questionnaires, and observations. The product feasibility is carried out by media experts, material experts and students. The results obtained from experts and students showed that the media developed showed feasibility as a learning medium.